Chilean R&D Policy - Serra, Pablo (Estudios de Economía, 2016)
This paper analyzes Chilean research and development (R&D) policy. To do so, it describes the institutions responsible for policy design and implementation as well as those which conduct R&D. In addition, it addresses the R&D policy and the instruments used to carry it out. The analysis is based on market failures justifying State intervention in R&D. The policy instruments used in Chile respond broadly speaking to market failures in R&D. Where there is a greater deficit is at the institutional level as there are many institutions, which are in no way interrelated, that are responsible for defining and conducting the science and technology policy.